Balancing the Socio-political and Medico-ethical Dimensions of HIV A Social Public Health Approach - Laar, Amos.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
Responding to public health challenges at the global and local levels can give rise to an array of tensions. To assure sustainable public health, these tensions need to be meaningfully balanced. Using empirical evidence and lived experiences relating to HIV from the global south, this book enunciates the many dimensions of national-level responses to HIV/AIDS including conceptual, philosophical, and methodological perspectives from public health, public policy, bioethics, and social sciences. Calling out glaring neglects, the book makes a bold recommendation for the destabilization of the naturalness with which national HIV/AIDS responses ignore the socio-political and medico-ethical dimensions of HIV. The case made is grounded in the philosophy of social public health. Such a critical perspective is not unique to Ghana$1 (Bs response to HIV/AIDS but serves as emblematic voice for similarly situated settings of the global south. The book is also timely. It is written at a time when public health actors are repositioning themselves to be competent users of not only pharmaceutic vaccines, but also social vaccines. Topics explored in the chapters include: Public health approaches to HIV and AIDS Access to life-saving public health goods by persons infected or affected by HIV (3z(BThey are criminals(3y(B: AIDS, the law, harm reduction, and the socially excluded Developing socially and ethically responsive National AIDS policies Balancing the Socio-political and Medico-ethical Dimensions of HIV: A Social Public Health Approach is compelling reading for a broad spectrum of readers. The book will appeal to professionals, scholars, and students in public health, public policy, bioethics, and social sciences, as well as medical anthropologists, sociologists, and global health scholars. Public health economists, lay politicians, and civil society organizations advocating for health equity will find the book useful as well. .s
CHAPTER 1: The practice of public health -- CHAPTER 2: Public health approaches to HIV and AIDS -- CHAPTER 3: HIV interventions: which should count? which should not? And why not? -- CHAPTER 4: Access to life-saving public health goods by persons infected or affected by HIV -- CHAPTER 5: (3z(BThey are criminals(3y(B: AIDS, the law, harm reduction, and the socially excluded -- CHAPTER 6: Developing socially and ethically responsive National AIDS policies -- CHAPTER 7: Making National HIV/AIDS response responsive to social public health: Lessons from Ghana.s
Keywords: Public health; Social structure; Equality; Diseases; Medical Ethics; International economic relations; Political planning; Public Health; Social Structure; Diseases; Medical Ethics; International Political Economy$1 (B.s; Public Policy; Acquired Immunodeficiency Syndrome